Lost dogs and Lonely Hearts - Dillon, Lucy (London Hodder, 2009)
Thirty-nine year old Rachel is having a really bad year. After losing her job and breaking up with her boyfriend, Rachel has inherited her late aunt's house, her beloved border collie, and a crowded rescue kennel, despite the fact that she knows almost nothing about dogs.
Keywords: Single women -- Animal shelters -- Human-animal relationships